U.S. unemployment insurance through the Covid-19 crisis - Francesco Spadafora (Journal of Government and Economics (JGE), 2023)
The Unemployment Insurance (UI) system in the United States has played a decisive lifeline role in effectively mitigating the economic and social impact of the Covid-19 pandemic, which prompted the largest expansion of UI programs in history, one that is unprecedented in scope, scale and cost. However, the crisis has once again exposed some well-known challenges of the program, perhaps best epitomized by the steady decline since the 1980s of both the recipiency rate and the wage replacement rate, which is partly related to the UI system's funding structure. As a result, on the eve of the pandemic less than one in three unemployed workers used to collect UI benefits - of lower amounts and often for shorter periods of time than before - despite that the average duration of unemployment had almost doubled in the aftermath of the Great Recession. The pandemic has also laid bare additional shortcomings - most notably in the effectiveness of the UI delivery infrastructure to provide timely and accurate payments - which have prompted further calls for modernizing the UI system. The objective of this paper is threefold: first, after a brief description of the main structural characteristics of the UI system, it compares the role played by UI in mitigating the impact of the 2008-09 Great Recession and the 2020 Covid-19 pandemic; second, it reviews the empirical evidence from the pandemic on potential demand-side (countercyclical stabilization) and supply-side (job-search disincentives) effects of emergency extensions of UI programs. Finally, it discusses the main lessons that the expansion of UI programs to respond to the pandemic can offer to inform - and enrich - the debate on whether and how to reform the UI system. The experience with the UI system provides fundamental lessons that can usefully inform the debate on whether and how to introduce - for example in Europe - a common unemployment insurance scheme for macroeconomic stabilization.
Keywords: E24; H7; J64; J65; 330; CARES Act; Countercyclical stabilization; Covid-19; Job acceptance; Unemployment; Unemployment insurance